森林伦理和多价值森林管理 - Coufal, James E., author; Rolston, Holmes, 1932-2025, author; Institute of Philosophy, publisher (Colorado State University. Libraries, 1999)
The Society of American Foresters (SAF) has long had an ethic of using forests to benefit society. Now many foresters, prompted by Aldo Leopold and his land ethic, are wondering if SAF does not need a forest ethic, respecting the integrity of natural systems, to complement its ethic for society. Forests are communities as well as commodities. Forest management ought to expand from an ethical of multiple use to one of protecting multiple values found in forests.
A forest ethic and multivalue forest management
Sen lin lun li he duo jia zhi sen lin guan li
Text in Chinese.
James Coufal, co-author, is in the College of Environmental Science and Forestry, State University of New York, Syracuse, and is former president of SAF.
Keywords: environmental ethics; ethical aspects; forests and forestry; forest management; moral aspects